Evaluation of an interactive educational system in urban knowledge acquisition and representation based on students' profiles. Issue 5 (2nd May 2020) - Sanchez‐Sepulveda, Monica V.; Fonseca, David; García‐Holgado, Alicia; García‐Peñalvo, Francisco José; Franquesa, Jordi; Redondo, Ernesto; Moreira, Fernando
Abstract: The aim of this article is to study how students currently understand the conception of space through different media and how that understanding helps them to intervene in the space. Firstly, the process of teaching and learning as well as innovative supporting technologies are analysed, revealing the characteristics of the contemporary student profile and better ways of teaching according to it. Secondly, we describe the evaluation of an experiment with a virtual reality (VR) system for urban project design with students of architecture from two universities. The premise is that the technology used in VR is familiar to the current profile of students. This paper aims to study the advantages and disadvantages of this trend and to find a balance. To do so, we use a quantitative method to evaluate students' profiles and their level of satisfaction with the system. The results were obtained by a questionnaire and a survey, which show the role and use of technologies in the students' environment and the degree of satisfaction when using it in the educational processes. In line with our assumptions, the value of satisfaction in the use of an advanced visualization technology in the classroom reveals a high level of motivation, in general, with differentiation between students in their first and last phases of studies.